GEOSPATIAL DASHBOARD FOR PROBLEM REPORTER IN JAMBI PROVINCE - Prasaja, Ahmad Syukron; Syaiful Huda, Imam Arifa'illah (JUSIM (Jurnal Sistem Informasi Musirawas), 2023)
Community involvement in providing problem reports is essential to improving the quality of life in cities and villages. Jambi already has "SiKESAL" as a problem-reporting application in Jambi, but it has not been able to provide information on the spatial distribution of locations through a single dashboard display. This research aims to apply the Geospatial Dashboard application as a spatial-based problem-reporting application using ArcGIS technology from ESRI. Sampling as information on problem topics for the development of the Geospatial Dashboard includes road damage, availability of disability facilities in houses of worship, illegal waste disposal sites, illegal parking, and road damage. The development of this Geospatial Dashboard presents the distribution, number, range, trend, and centre of problems so that it can be used for direct monitoring, decision-making, and solving related departmental problems. The study results show that the development of the Geospatial Dashboard can create data integration between sectors in real-time or quickly and assist local governments in solving various problems in Jambi Province.